Pleural Empyema and Aortic Aneurysm: A Retrospective National Population-Based Cohort Study. Issue 47 (November 2015) - Wu, Ching-Yang; Su, Ta-Wei; Huang, Kuo-Yang; Ko, Po-Jen; Yu, Sheng-Yueh; Kao, Tsung-Chi; Shen, Te-Chun; Chou, Tzu-Yi; Lin, Cheng-Li; Kao, Chia-Hung
Abstract : Abstract: Pleural empyema (PE) may evolve into necrosis, fistula in the thorax, and sepsis; thus, it is also associated with high mortality. We investigated and analyzed the risk of aortic aneurysm (AA) in a cohort study of patients with PE. A total of 34, 250 patients diagnosed with PE were identified as the PE cohort, and 137, 000 patients without PE were selected randomly as the control group and matched by sex, age, and index year of PE diagnosis. Patients ages 20 years and younger with a history of AA were excluded. The risk of AA was analyzed using a Cox proportional hazards regression model. Excess risk of AA development was 1.69-fold higher in PE patients (adjusted hazard ratio [aHR] = 1.69; 95% confidence interval [CI] = 1.39–2.05) compared with non-PE patients. The patients with PE exhibited a greater adjusted risk of AA (aHR = 2.01; CI = 1.44–2.81) even if they did not have any of the 9 comorbidities included in our analysis (diabetes, hypertension, hyperlipidemia, chronic obstructive pulmonary disease, heart failure, cardiac artery disease, stroke, bacterial endocarditis, and rheumatic endocarditis). Compared with the patients without any of the 9 comorbidities or PE, the patients with only PE had a greater risk of developing AA (aHR = 2.00; CI = 1.43–2.79). The PE cohort had a significantly higher cumulative incidence of AA than the non-PE cohort did during 12 years of follow-up. In a large-scale cohort, patients with PE are linked with an increased risk of AA.